Metastatic MHC class I-negative mouse cells derived by transformation with human papillomavirus type 16 - Smahel, M; Sobotková, E; Bubeník, J; Símová, J; Zák, R; Ludviková, V; Hájková, R; Kovarík, J; Jelínek, F; Povýsil, C; Marinov, J; Vonka, V (British journal of cancer, 2001)
In the endeavour to develop a model for studying gene therapy of cancers associated with human papillomaviruses (HPVs), mouse cells were transformed with the HPV type 16 (HPV16) and activated H-ras oncogenes. This was done by cotransfection of plasmid p16HHMo, carrying the HPV16 E6/E7 oncogenes, and plasmid pEJ6.6, carrying the gene coding for human H-ras oncoprotein activated by the G12V mutation, into secondary C57BL/6 mouse kidney cells. An oncogenic cell line, designated MK16/1/IIIABC, was derived. The epithelial origin of the cells was confirmed by their expression of cytokeratins. No MHC class I and class II molecules were detected on the surface of MK16/1/IIIABC cells. Spontaneous metastases were observed in lymphatic nodes and lungs after prolonged growth of MK16/1/IIIABC-induced subcutaneous tumours. Lethally irradiated MK16/1/IIIABC cells induced protection against challenge with 10(5) homologous cells, but not against a higher cell dose (5 x 10(5)). Plasmids p16HHMo and pEJ6.6 were also used for preventive immunization of mice. In comparison with a control group injected with pBR322, they exhibited moderate protection, in terms of prolonged survival, against MK16/1/IIIABC challenge (P < 0.03). These data suggest that MK16/1/IIIABC cells may serve as a model for studying immune reactions against HPV16-associated human tumours.
Keywords: MHC antigeny I. třídy; Male; transformované buněčné linie; onkogenní proteiny virové; Tumor Cells, Cultured; Mice, Inbred C57BL; Animals; keratiny; represorové proteiny; Humans; Immunohistochemistry; Mice; exprese genu; myši inbrední C57BL; ras Proteins; Plasmids; imunoblotting; Papillomaviridae; virová transformace buněk; mužské pohlaví; DNA, Recombinant; MHC antigeny II. třídy; Female; Immunoblotting; Papillomavirus E7 - proteiny; RNA; Keratins; rekombinantní DNA; experimentální nádory; Ras proteiny; metastázy nádorů; ženské pohlaví; Cell Line; Cell Transformation, Viral; Histocompatibility Antigens Class I; Neoplasm Metastasis; nádorové buňky kultivované; Flow Cytometry; zvířata; Histocompatibility Antigens Class II; Gene Expression; transplantace nádorů; průtoková cytometrie; Transfection; imunohistochemie; transfekce; Neoplasms, Experimental; polymerázová řetězová reakce s reverzní transkripcí; lidé; Repressor Proteins; plazmidy; Neoplasm Transplantation; buněčné linie; Reverse Transcriptase Polymerase Chain Reaction; Oncogene Proteins, Viral; Cell Line, Transformed; myši; Papillomavirus E7 Proteins